The impact of electronic advertising on the purchase decision for hotel services (a field study in Tartous hotels) - شوباصي شعبان (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aimed to study the effect of electronic advertising on the purchase decision for hotel services, by conducting a field study in Tartous hotels, where third- and fourth-class hotels were selected. This study relied on the descriptive analytical approach. A questionnaire was designed and distributed to a random sample consisting of (106) Tourists who are guests and users of social networking sites in hotels in Tartous Governorate. The data collected was analyzed and hypotheses were tested using the SPSS program.25. The study also reached a set of results, namely that the content of the electronic advertisement through social media had the greatest impact on the decision to purchase hotel services, then followed by the credibility of the electronic advertisement, and then the design of the electronic advertisement, while the design of the electronic advertisement through the website on the purchase decision for hotel services services had less impact compared to the other dimensions.